FAKTOR-FAKTOR PERCERAIAN PADA MASYARAKAT MUSLIM KOTA PALU (ANALISIS SOSIOLOGIS) - Sitti Nurkhaerah; Hamiyuddin Hamiyuddin (Qaumiyyah: Jurnal Hukum Tata Negara, 2020)
The phenomenon of divorce is also inseparable from various causes, so that it becomes the reason for husband or wife to file for divorce at the religious court. In addition, the impact of divorce will have a major influence on the psychology of parties, the environment and the children are no exception. Specifically in Central Sulawesi, the number of divorces that occurred during 2016 was 2,699 cases handled by the Religious Courts in 13 districts and cities. This figure has increased when compared to 2015 only 2,490 cases. In addition, from this overall figure, it is noted that wives dominate filing for divorce compared to husbands.